Sobre a possibilidade de um diálogo entre jean-jacques rousseau e arthur schopenhauer através da escrita: do sentimento natural de piedade à ética da compaixão. - CASTRO, Klisman Lucas de Sousa (2021)
The aim of this paper is to explain the approximation between Jean-Jacques Rousseau and Arthur Schopenhauer through writing. In the 18th century, with the purpose of dispelling the false opinions and impressions made about him, Rousseau expresses the desire to present himself in a faithful way to his contemporary readers. To this end, as Maurice Blanchot indicates, he develops a new proposal for literature that surpasses the traditional literary molds practiced until then. Autobiographical writing, according to Jean Starobinski, is used by the Geneva author to present the immediate feeling and a resource to achieve the desired transparency. On the flip side, in the 19th century, after suffering from discredit and oblivion due to the irrationalist essence of his philosophy, Arthur Schopenhauer develops a literary criticism to denounce the decline of writing in his time. For him, as Rüdiger Safranski states, this criticism is associated with the crisis caused by the way modern authors think, directly influencing the degeneration of writing and style. That’s why, Jair Barboza shows that the German philosopher is reacting to the systematic philosophy of the post-Kantian thinkers, who defend reason as the principle of the world. Therefore, he proposes another type of production to the authors, so that they could establish a more direct and honest communication with the readers. Because of these undertakings, both Rousseau and Schopenhauer suffer from isolation and are subjected to condemnations, censures, and reproaches, which will allow us to understand that the moral philosophy of both is fundamental for them to continue writing. In general terms, the relationship between the feeling of pity and compassion explains why they persisted in denouncing the evils and vices of the societies in which they lived. Thus, we intend to demonstrate the transformations of these moral concepts and how they function in the process of identification with the condition of those who suffer. Therefore, Rousseau's autobiographical set and Schopenhauer's criticism of writing represent the search for the clarity of truth, through which they were led to describe their own portraits and truly manifest themselves to their readers.